Dirac System with Discontinuities at Two Points - Fatma Hıra; Nihat Altınışık (Abstract and Applied Analysis)
We deal with a regular Dirac system which has discontinuities at two points and contains eigenparameter in a boundary condition and two transmission conditions. We investigate asymptotic behaviour of eigenvalues and corresponding eigenfunctions of this Dirac system and construct Green’s function.